Aquisição de segunda língua: abordagens formais e abordagens sócio-interacionistas - Corsetti, Cristiane Ruzicki (BELT - Brazilian English Language Teaching Journal, 2011)
This article describes language and second language acquisition theories. Behaviourism indicates that it is possible to predict verbal behaviour based on variables such as stimulus, response and reinforcement. The nativist or generativist theory assumes that language learning is independent from cognition while the interactional theory places language learning within cognition. Formal approaches to second language acquisition assume the existence of an innate universal grammar, but they differ with regard to the starting point of second language acquisition. Krashen’s input hypothesis (1985) highlights the importance of comprehensible input in second language acquisition and in the acquisition of communicative competencies. Social interactional theories emphasise the impact of the social context on language. We conclude that formal theories account for speakers’ linguistic creativity whereas social interactional theories detail the acquisition of the communicative aspects of language as these are socially context-dependent.